(untitled) (Cadernos de Linguagem e Sociedade, 2013)
GUERRA, V. M. L.; ENEDINO, W. C.; NOLASCO, E. C. (Orgs.). Estudos de linguagens: diversidade e ensino. São Carlos: Pedro & João Editores, 2012. 280p.